The Accuracy of Direct Targeting Using Fusion of MR and CT Imaging for Deep Brain Stimulation of the Subthalamic Nucleus in Patients with Parkinson's Disease - Almahariq, Fadi; Sedmak, Goran; Vuletić, Vladimira; Dlaka, Domagoj; Orešković, Darko; Marčinković, Petar; Raguž, Marina; Chudy, Darko (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Introduction In 33 consecutive patients with Parkinson's disease (PD) undergoing awake deep brain stimulation (DBS) without microelectrode recording (MER), we assessed and validated the precision and accuracy of direct targeting of the subthalamic nucleus (STN) using preoperative magnetic resonance imaging (MRI) and stereotactic computed tomography (CT) image fusion combined with immediate postoperative stereotactic CT and postoperative MRI, and we report on the side effects and clinical results up to 6 months' follow-up.Materials and Methods Preoperative nonstereotactic MRI and stereotactic CT images were merged and used for planning the trajectory and final lead position. Immediate postoperative stereotactic CT and postoperative nonstereotactic MRI provided the validation of the final electrode position. Changes in the Unified Parkinson's Disease Rating Scale III (UPDRS III) scores and the levodopa equivalent daily doses (LEDD) and appearance of adverse side effects were assessed.Results The mean Euclidian distance (ED) error between the planned position and the final position of the lead in the left STN was 1.69 ± 0.82 mm and that in the right STN was 2.12 ± 1.00. The individual differences between planned and final position in each of the three coordinates were less than 2 mm. The UPDRS III scores improved by 75% and LEDD decreased by 45%. Few patients experienced complications, such as postoperative infection (n = 1), or unwanted side effects, such as emotional instability (n = 1).Conclusion Our results confirm that direct targeting of an STN on stereotactic CT merged with MRI could be a valid method for placement the DBS electrode. The magnitude of our targeting error is comparable with the reported errors when using MER and other direct targeting approaches.
Keywords: STN; deep brain stimulation; Parkinson's disease; UPDRS III; stereotactic surgery